"El Provenir del Pasado" la novela nicaragüense entre historia canonizada, lucha representacional y pluralidad de lecturas - Gianni, Silvia (2016)
History is an important source for inspiration for Nicaraguan narrative because it is one space where literature defines its social function. In this study I intend to present a panorama of the different forces present in the Nicaraguan literary field. I analyze the confrontation between the cultural powers of Vanguardism, a cultural tradition uses history in its representational struggle and a third tendency, one that dialogues with the reader through the reconstruction of fragments of the past.